Inequality and Economic Growth: European Versus U.S. Experiences - Reto Foellmi; Josef Zweimüller (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper discusses long-term trends in the macroeconomic growth performance and in income distribution in Europe and the U.S. We review insights from the recent macroeconomic literature on inequality and growth and use these insights to shed light on the growth and inequality trends
Keywords: 330